MEDIATISASI DAN REPRESENTASI PARIWISATA SEMBALUN DI AKUN INSTAGRAM @INSIDESEMBALUN - I Ketut Putu Suardana; Ni Luh Senja Harining; Ni Nyoman Puji Artini (Institut Agama Hindu Negeri Gde Puda Mataram, 2026)
This study analyzes the representation of Sembalun tourism through content published on the Instagram account @insidesembalun. Employing a qualitative approach with a descriptive-interpretative method, data were collected through non-participant observation of Instagram content, including photos, videos, captions, and user interactions. The findings reveal that Sembalun tourism is predominantly represented through aesthetically pleasing and curated visuals of natural landscapes, creating an image of the destination as exotic and instagrammable. Audience participation through user-generated content reflects a collective production of meaning, although it remains shaped by the account's curation process. Furthermore, the mediatization of tourism via Instagram contributes to the commodification of the destination, positioning Sembalun as a visual product within the digital tourism market. This study concludes that Instagram functions not only as a promotional medium but also as an agent of reality construction that shapes perceptions, expectations, and tourism practices. Consequently, tourism communication strategies should prioritize not only visual appeal but also environmental sustainability and local socio-cultural values.